PRINCIPLE OF POINT MAKING OF MULTI-PROJECTION PREDICTIVE DECISION - Olga N. Lapaeva (Статистика и экономика, 2016)
The principle of point making of multi-projection predictive decision in economics is set forth in the article. The principle envisages searching for the best variant in each projection and result making by crossing of partial sets